Modification of Gypsum Binders by Using Carbon Nanotubes and Mineral Additives. (2017) - Tokarev, Yurii; Ginchitsky, Evgeniy; Sychugov, Stanislav; Krutikov, Vyacheslav; Yakovlev, Grigoriy; Buryanov, Alexander; Senkov, Sergey
Abstract: The investigation results of physical and mechanical properties and structure of gypsum samples modified by single-wall carbon nanotubes together with other additives – Portland cement, microsilica and metakaolin are given. When analyzing the results of mechanical tests, it was demonstrated that when applying the additive complex containing carbon nanotubes and ultrafine additive the improved mechanical characteristics are observed in opposition to the separate application of additives. The microstructure analysis of reference and modified samples allowed revealing the availability of new formations in the sample structure and changes in the morphology and sizes of crystalline hydrates.